Prevalence of cognitive and functional impairment in community-dwelling elderly: importance of evaluating activities of daily living Prevalência de comprometimento cognitivo e funcional em idosos residentes em uma comunidade: importância da avaliação das atividades de vida diária - Jerson Laks; Elienai Maria Rubim Batista; Elza Rocha Lima Guilherme; Ana Lúcia Barros Contino; Maria Eliete Vieira Faria; Claudia Soares Rodrigues; Estevão de Paula; Eliasz Engelhardt (Arquivos de Neuro-Psiquiatria)
The study aims to evaluate the prevalence of cognitive/functional impairment in community-dwelling elderly above 60 years of age (n= 870; m=297, f=573) and the relationship of age, gender, and functional impairment with cognitive impairment using Mini-Mental State Examination (MMSE) and Pfeffer Functional Activities Questionnaire (PFAQ). Chi-square and Student's tests were used to compare cognitive and functional deficits. Linear regression assessed MMSE/PFAQ relationship. Stratified analysis assessed confounding factors. Logistic regression assessed the relationship among age/gender/functional status with cognitive impairment (p<0.05). Prevalence of cognitive/functional impairment was 19.2%. Functional and cognitive impairment are negatively correlated (Pearson= 0.737), despite educational level (illiterate/literate: OR=15.60; p=0/OR = 16.40; p=0). Age and gender (female) were associated with cognitive/functional impairment. Functional impairment is highly correlated to cognitive impairment. Family/health professionals may recognize functional impairment more easily than cognitive impairment. Thus, the use in combination of cognitive and functional scales is important when screening for dementia. O estudo objetivou avaliar a prevalência de comprometimento cognitivo/funcional em idosos acima de 60 anos (n= 870; m=297, f=573) residentes na comunidade e avaliar a relação entre idade, gênero e comprometimento funcional com o comprometimento cognitivo. Utilizou-se o Mini-Exame do Estado Mental (MEEM) e o Questionário de Atividades Funcionais de Pfeffer (PFAQ). Comparou-se relação de deficits cognitivo e funcional (MEEM e PFAQ). A prevalência de comprometimento cognitivo/funcional foi 19,2%. Há relação entre comprometimento cognitivo e funcional (Pearson=0,737), independente do nível educacional (analfabetos/alfabetizados: OR=15,60; p=0/ OR = 16,40; p=0). Idade e gênero são fatores associados a comprometimento cognitivo/funcional (p<0,05). A prevalência de comprometimento cognitivo/funcional é mais alta que a encontrada em outro estudo brasileiro. Idade, gênero feminino e comprometimento funcional estão diretamente associados a comprometimento cognitivo. O reconhecimento de comprometimento funcional pode ser mais fácil por familiares/profissionais de saúde. Isso reforça a idéia do uso combinado de escalas em rastreamentos de demência.